The motherhood constellation : a unified view of parent-infant psychotherapy - Stern, Daniel N. (Karnac Books, 1998)
The author addresses the field of infant mental health. He draws on his experience - in both the lab and the clinic - to present an integrated model of treatment for both infants and their parents.